Voxel‐based morphometry study on monozygotic twins discordant for Alzheimer's disease. (15th September 2015) - Rossi, R.; Pievani, M.; Järvenpää, T.; Testa, C.; Koskenvuo, M.; Räihä, I.; Kaprio, J.; Frisoni, G. B.; Rinne, J. O.; Laakso, M. P.
Abstract : Objectives: We set to investigate the possible role of genes and environment in developing Alzheimer's disease (AD) in monozygotic twin pairs discordant for AD. Methods: Three pairs of twins discordant for AD, who were enrolled in the Finnish Twin Cohort, were used in the study and compared with 13 controls. Gray matter changes were assessed with magnetic resonance images using voxel‐based morphometry with statistical parametric mapping. Results: In the affected twins, the peaks of volume loss were located bilaterally in the temporal (including the hippocampus), the frontal, and the parietal lobes, while in the unaffected siblings, the peaks were located in the frontal gyri and in the parietal lobule. Thus, in the unaffected twins, the pattern of volume loss overlaps with the neocortical but not with the medial temporal areas. Discussion: These findings suggest that genetic factors more largely control neocortical regions, whereas environmental factors more strongly affect medial temporal regions.